Effect of Intravenous Magnesium Sulfate and Fentanyl Citrate on Circulatory Changes During Anaesthesia and Surgery: A Clinical Study - Dilip Kothari; Amrita Mehrotra; Bhanu Choudhary; Alok Mehra (Indian Journal of Anaesthesia, 2008)
The study was conducted to compare the effects of magnesium sulfate and fentanyl citrate on circulatory variables during anaesthesia and surgery. Sixty patients (ASA-I& II) of either sex, between the age of 25-45 years were given either magnesium sulfate (Group M, n=30) 20mg.kg -1 5 min before induction, 10 mg.kg -1 5 min before skin incision and 10 mg.kg -1 every 30 min interval or fentanyl citrate (Group F, n=30) 1.25 mcg.kg -1 , 0.5 mcg.kg -1 and 0.5 mcg.kg -1 at similar time intervals. Balanced general anaesthesia was maintained with O2:N2O + halothane 0.2% and relaxants throughout the study period with controlled ventilation. Changes in pulse rate (PR), systolic blood pressure (SBP), diastolic blood pressure (DBP) and mean arterial pressure (MAP) were recorded at various time intervals. A clinically significant rise in pulse rate (+11.3%) was recorded in Group M after initial injection. Statistically insignifi-cant rise in all haemodynamic variables from baseline values were recorded immediately after intubation in both the groups, after which they returned and maintained, nearer to baseline values. No sympatho-somatic responses like tearing, sweating, eye movement etc. were observed during the course of study. In conclusion, the clinical results suggest that magnesium sulfate could be a safe and cheaper alternative analgesic to fentanyl citrate during general anaesthesia.